Development report on China's new media - Tang, Xujun; Wu, Xinxun; Huang, Chuxin; Liu, Ruisheng (Research series on the Chinese dream and China's development path., 2017)
In this book, specialists and scholars present a comprehensive account of the latest developments in Chinese new media. The articles explore important areas such as security of cyberspace in China; the development of WeChat and micro-blogs; public opinions of social media and the transformation of traditional media. It also summarizes the development of the new-media industry, including digital TV, mobile games, the online video industry, IPTV, new-media advertising and mobile news applications. It is a valuable reference work for researchers and professionals working in media.